Osteoprotective effect of combination therapy of low-dose oestradiol with G15, a specific antagonist of GPR30/GPER in ovariectomy-induced osteoporotic rats. Issue 4 (18th August 2015) - Kang, Wen-Bo; Cong, Yu; Ru, Jiang-Ying; Ying, Si-Qi; Zhu, Ting; Wang, Dong-Sheng; Liu, Xiao-Wei; Liu, Gang; Zhao, Jian-Ning
Abstract : Administration of low-dose oestradiol (E2) combining G15, this combination therapy may be an effective supplement of drugs in prevention and treatment for postmenopausal osteoporosis. Abstract : Identified and cloned in 1996 for the first time, G protein-coupled oestrogen receptor (ER) 30 (GPR30/GPER) has been a hot spot in the field of sex hormone research till now. In the present study, we examined the effects of low-dose oestradiol (E2) combined with G15, a specific antagonist of GPR30 on ovariectomy (OVX)-induced osteoporosis in rats. Female Sprague–Dawley (SD) rats undergoing OVX were used to evaluate the osteoprotective effect of the drugs. Administration of E2 [35 μg/kg, intraperitoneally (ip), three times/week) combining G15 (160 μg/kg, ip, three times/week) for 6 weeks was found to have prevented OVX-induced effects, including increase in bone turnover rate, decrease in bone mineral content (BMC) and bone mineral density (BMD), damage of bone structure and the aggravation in biomechanical properties of bone. The therapeutic effect of these two drugs in combination was better than that of E2 alone. Meanwhile, the administration of G15 prevented body weight increase or endometrium proliferation in the rats. In conclusion, administration of low-dose E2 combining G15 had a satisfactory bone protective effect for OVX rats, without significant influence on body weight or the uterus. This combination therapy may be an effective supplement of drugs in prevention and treatment for postmenopausal osteoporosis.